(untitled) (Bioscience Journal, 2018)
Because the consumption and use of native fruit, there is need for research on strategies for maintenance propagation of the species. Jatoba is a fruitful tree of great importance to the Brazilian fauna, cuisine and reclamation and thus is essential to obtain high quality seedlings. This study aimed at the formation of Jatoba seedlings on different substrates. The experiment was conducted at Experimental Farm for Teaching, Research and Extension of UNESP, Campus Ilha Solteira, SP, located in Selvíria/MS for the period 13 October 2011 to 11 February. For producing the seedlingsm we used a black screen of polypropylene (Sombrite®) with 50% light reduction and black plastic bags 15 x 21,5 cm (1.8 L) filed with different substrates: (S1) soil control; (S2) soil (50%) + manure (50%); (S3) soil + mineral fertilizer; (S4) soil (50%) + mineral fertilizer + manure (50%); (S5) soil + limestone; (S6) soil (50%) + limestone + manure (50%); (S7) soil + mineral fertilizer + limestone; (S8) soil (50%) + limestone + manure + mineral fertilizer (50%). Emergence of seeds was evaluated daily and fortnightly and after emergence of seeds were observed height and stem diameter. At 120 days after emergence, we evaluated the length of root system, shoot and root dry mass, total dry mass, shoot/ lap diameter (S/D), relation between shoot and root dry mass (SDM/RDM), relation between shoot and root fresh mass (SFM/RFM), relation between length of shoot/root (LS/LR) and Dickson’s Quality Score (DQS). Experimental design was completely randomized in factorial with 8 x 7 reviews substrates. Proceeded with analysis of variance unfolding of significant interactions with the Tukey test for comparisons of means of the substrate factor and time factor for polynomial regression. Treatment pure soil substrate (S1) provided to the Jatoba seedlings the largest biomass formation of shoot and root dry mass. The addition of manure to the substrate did not benefit the development of the Jatoba seedlings.